Tapol : . Tapol bulletin : British campaign for the release of Indonesian political prisoners
Also titled: Tapol bulletin. Since no.78 titled: Tapol : the Indonesia human rights campaign. See also: Tapol. U.S. Campaign ... (ZK 37582).